Performance evaluation of high-elasticity asphalt mixture containing inorganic nano-titanium dioxide for applications in high altitude regions. (28th February 2019) - Zheng, Dong; Qian, Zhen-dong; Li, Pan; Wang, Lin-bing
Highlights: Using Nano-TiO2 in asphalt improves the rheological property and aging resistance. MHEA mixture has superior resistance to rutting and low-temperature cracking. MHEA mixture performs excellently in recurrent freeze-thaw cycle resistance. Abstract: To resist the strong solar ultraviolet (UV) radiation and large temperature/moisture fluctuation in high altitude regions, a high-elasticity asphalt (HEA) mixture containing inorganic Nano-titanium dioxide (Nano-TiO2 ) is proposed. This paper presents a laboratory study on the performance of Nano-TiO2 modified HEA asphalt (MHEA) and MHEA mixtures. Rheological properties and UV-aging resistance of asphalt binder were first assessed using dynamic shear rheometer, bending beam rheometer and UV weathering oven. Furthermore, mixture properties, including rutting resistance, low-temperature cracking resistance, moisture stability, UV-aging resistance and recurrent freeze-thaw cycle resistance, were evaluated in the laboratory. Results show that addition of Nano-TiO2 can improve the high-temperature rheology and UV-aging resistance of HEA asphalt, with no obvious influence on low-temperature rheology. In addition, When MHEA asphalt is used, the rutting resistance and low-temperature cracking resistance can be improved approximately to twice that of styrene–butadiene–styrene (SBS) mixture. In term of recurrent freeze-thaw cycle resistance, MHEA mixture performs better than SBS mixture, as reflected in smaller void structure damage, higher tensile strength ratio and lower freeze-thaw damage ratio at the same freeze-thaw cycles. The findings indicate that MHEA mixture has a great potential to be applied in asphalt pavement in high altitude regions.